Patrimonial Politics as a Functional Threat to Good Governance and Development in West Africa (Global Journal of Human-Social Science, 2015)
Abstract not found
Keywords: patrimonial politics; Africa; weak institutions; strong personality; stomach infrastructure; Nigeria